Role of pelvimetry in active management of labour. Issue 5995 (29th November 1975) - Joyce, D N; Giwa-Osagie, F; Stevenson, G W
Abstract : All cases referred for pelvimetry in 1970-1 and all breech presentations referred for pelvimetry in 1972-4 were reviewed. Indications for pelvimetry fell into four main categories: high head in the antenatal clinic (47-8%); high head in labour (13-9%); breech presentation (20-9%); and previous caesarean section (14-8%). In the first two categories pelvimetry rarely if ever influenced management, and it should not be performed routinely. In breech presentation and cases of caesarean section pelvimetry seemed to be of value, but in the latter group it should be performed puerperally to avoid the known radiation hazard to the fetus. A fairly close correlation between obstetric conjugate and pelvic capacity was shown, which suggested that a 3400-g baby might pass through a pelvis of obstetric conjugate of 10 cm as a cephalic trial of labour, but would need an obstetric conjugate of 11-7 cm for safe vaginal breech delivery.